Contrasting responses in community structure and phenology of migratory and non-migratory pollinators to urbanization - Luder, K.; Knop, E.; Menz, Myles (Blackwell Science Ltd, 2018)
Aim: Anthropogenic landscape change, such as urbanization, can affect community structure and ecological interactions. Furthermore, changes in ambient temperature and resource availability due to urbanization may affect migratory and non-migratory species differently. However, the response of migratory species to urbanization is poorly investigated, and knowledge for invertebrates in particular is lacking. Our aim was to investigate whether there was a shift in community structure and phenology of hoverflies in urban landscapes, depending on migratory status. Location: Switzerland. Methods: Using a paired design, we compared urban and rural landscapes to investigate the impact of urbanization on the abundance, diversity and phenology of hoverflies. Furthermore, we tested whether migratory and non-migratory species responded differently to urbanization. Results: We observed a difference in the response of migratory and non-migratory hoverfly communities. Although the abundance of hoverflies was higher in the rural ecosystem, driven by a high abundance of migratory species, there was no difference in species richness between the land use types. However, the community structure of non-migratory species was significantly different between urban and rural ecosystems. The phenology of hoverflies differed between the two ecosystems, with an earlier appearance in the year of migratory species in urban landscapes. Main conclusions: To our knowledge, this is the first study to investigate the response of migratory insect communities to urbanization. We demonstrated that migratory and non-migratory hoverflies respond differently to urbanization. This highlights the importance of differentiating between trait and mobility groups to understand community assemblage patterns in anthropogenic landscapes. The differences in phenology supports the growing evidence that urbanization not only affects the phenology of vegetation, but also affects the higher trophic levels. Changes in the phenology and community composition of species as a result of anthropogenic landscape change may have important implications for the maintenance of key ecosystem functions, such as pollination.